Fasudil Increases the Establishment of Somatic Cell Nuclear Transfer Embryonic Stem Cells in Mouse - Seongjun So; Mustafa Zafer Karagozlu; Yeonmi Lee; Eunju Kang (The Korean Society of Animal Reproduction and Biotechnology, 2020)
Somatic cell nuclear transfer derived embryonic stem cells (NT-ESCs) have significant advantages in various fields such as genetics, embryology, stem cell science, and regenerative medicine. However, the poor establishment of NT-ESCs hinders various research. Here, we applied fasudil, a Rho-associated kinase (ROCK) inhibitor, to develop somatic cell nuclear transfer (SCNT) embryos and establish NTESCs. In the study, MII oocytes were isolated from female B6D2F1 mice and performed SCNT with mouse embryonic fibroblasts (MEFs). The reconstructed NT-oocytes were activated artificially, and cultured to blastocysts in KSOM supplemented with 10 μM fasudil. Further, the blastocysts were seeded on inactivated MEFs in embryonic stem cell medium supplemented with 10 μM fasudil. A total of 26% of embryos formed into blastocysts in the fasudil treated group, while this ratio was 44% in the fasudil free control group. On the other hand, 30% of blastocysts were established NT-ESCs after exposure of fasudil, which was significantly higher than the control group (10%). The results suggest that fasudil reduced blastocyst development after SCNT due to inhibition of 2 cell cleavage while improved the establishment of NT-ESCs through the anti-apoptotic pathway.